2022
DOI: 10.3390/ijerph192113967
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Disordered Eating among Asian American College Students: The Role of Objectification through a Sociocultural Lens

Abstract: Disordered eating is a public health problem because it’s highly prevalent, dangerous, and costly. More research about its risk factors and mechanisms is needed to address this problem and prevent disordered eating among high-risk populations, particularly understudied ethnic minorities. The present study contributes to the limited existing research on acculturation and disordered eating among Asian American college students who represent an understudied and high-risk group. The sample consisted of 245 Asian A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Both studies found a significant relationship such that acculturative stress was associated with higher drive for thinness, thin-ideal internalization, or pressure for thinness [ 22 , 32 ]. In contrast, results from one study suggest a lack of significant relationship between acculturation and thin-ideal internalization [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies found a significant relationship such that acculturative stress was associated with higher drive for thinness, thin-ideal internalization, or pressure for thinness [ 22 , 32 ]. In contrast, results from one study suggest a lack of significant relationship between acculturation and thin-ideal internalization [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies examined the relationship between acculturation and body dissatisfaction or shame. Both found no relationship [ 24 , 33 ]. Kwan et al [ 22 ] found that acculturative stress was not associated with body dissatisfaction in a sample of ethnic minority undergraduate students.…”
Section: Resultsmentioning
confidence: 99%